A prospective study: Inflammation, infection and comorbidity in patients on long-term dialysis - DURMUŞOĞLU, LÜTFİYE; AKSU, MEHMET BURAK (My University, 2014)
SUMMARY: Background: The goal of this study was to identify inflammatory and infectious markers and their roles in mortality. Methods: We enrolled 111 patients on haemodialysis (HD) and collected data at three time points (baseline, 33 and 76 months). Results: Rates of Chlamydophila pneumoniae IgG, CRP ≥3mg/l, ESR >50mm/hour and fibrinogen >4g/l were, respectively, 63.1%, 60.4%, 48.6% and 42.3%. Mortality was 21.6% and 43.2% at 33 and 76 months where 58.3% of all deaths were cardiocerebrovascular (CCV) related. Non-survivors were older than survivors. Univariate analysis showed diabetes mellitus (DM) and cerebrovascular accident (CVA) as important for the 33-month all-cause mortality, and CRPlog, fibrinogen, ESR >50mm/hour, cardiovascular disease (CVD) and DM for the 76-month all-cause mortality. CVA was meaningful for the 33-month CCV mortality, and CVD, DM and ESR >50mm/hour for the 76-month CCV mortality. Kaplan-Meier revealed poorer survival for patients with ESR >50mm/hour at 76 months. Cox regression showed CVD, CVA and age as mortality predictors. Conclusion: Age, CVD and CVA are predictors for mortality in patients on HD patients, but the presence of C. pneumoniae IgG and inflammation are not. © 2013 European Dialysis and Transplant Nurses Association/European Renal Care Association.
Keywords: C-reactive protein; Erythrocyte sedimentation rate; Fibrinogen; Haemodialysis; Seropositivity of C. pneumoniae IgG